Scramble and Partitions for the Colonies of English, French, German, and Portuguese: A New Historicism Study of the African Continent - Usman, Abdulkarim; Imam, Yusuf Ismail (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper examines the scramble and partition of West African territories by European superpowers during the final two decades of the 19th century—a period that marked a turning point in the political and historical trajectory of the region. Drawing on secondary sources, the study analyzes the geopolitical rivalries and diplomatic tensions among major European powers, particularly Britain and France, in their quest to assert territorial control. It highlights key episodes, such as the Anglo-French conflict over South Africa, the disputes surrounding Egypt and the Gold Coast (present-day Ghana), and the broader imperial competition that fueled colonial expansion. The paper explores the underlying causes of the scramble, including economic interests, strategic rivalries, and national prestige, as well as the outcomes and consequences of the partition. Particular attention is given to the Berlin Conference of 1884–1885, which formalized European claims and codified rules for territorial acquisition, and to African resistance movements that challenged colonial imposition. The study concludes that the scramble and partition had profound and lasting effects on the political boundaries, governance structures, and socio-economic development of West African states. It recommends the promotion of civic education, political reforms, and pan-African engagement as pathways to restoring and safeguarding the continent’s autonomy and development, with specific reference to the Nigerian context.